Immune Checkpoint Targeted Therapy in Glioma: Status and Hopes - Qi, Yangzhi; Liu, Baohui; Sun, Qian; Xiong, Xiaoxing; Chen, Qianxue (Frontiers in Immunology, 2020)
Glioma is the most malignant primary tumor of the central nervous system and is characterized by an extremely low overall survival. Recent breakthroughs in cancer therapy using immune checkpoint blockade have attracted significant attention. However, despite representing the most promising (immunotherapy) treatment for cancer, the clinical application of immune checkpoint blockade in glioma patients remains challenging due to the ‘cold phenotype’ of glioma and multiple factors inducing resistance, both intrinsic and acquired. Therefore, comprehensive understanding of the tumor microenvironment and the unique immunological status of the brain will be critical for the application of glioma immunotherapy. More sensitive biomarkers to monitor the immune response, as well as combining multiple immunotherapies strategies, may accelerate clinical progress and enable development of effective and safe treatments for glioma patients.